Herbaceous ground vegetation in natural oak stands within south-east Forest-Steppe zone of Ukraine - Andrushchenko, O. P.; Rumіantsev M. Н.; Bondar, O. B. (Forestry and Forest Melioration, 2018)
Introduction Live ground cover is an integral part of forest ecosystems, which fixes and incorporates a significant amount of ash elements and nitrogen into the biological cycle. Moreover, it has a significant impact on the productivity and reforestation processes, as well as on the fertility of forest soils. Herbaceous vegetation is the place of life for forest animals, microorganisms and primary destructors of organic residues. It also has aesthetic, medicinal and floristic values. The aim of the research was to thoroughly study the productivity of forest stands within a specific forest type, in the formation of which the herbaceous ground vegetation plays an essential role. The first will ensure solving the key issues in forest management. Materials and Methods The study was conducted in mixed natural stands of seed origin at the age of 17, 42, 55, 79, 157 and 194 years under the conditions of the upland oak forest in the Skrypayivske Training & Experimental Forest Enterprise of the Kharkiv National Agrarian University named after V. V. Dokuchaiev. The stands grow on the right bank of the Siversky Donets River within the fresh and moist ash-lime oak forest site. To determine the biomass and species composition of the herbaceous ground vegetation within the stands, the technique of Rodin, Remezov, and Bazilevich was used, as well as the data of other researchers were taken into consideration. In total, 240 accounting areas were established under the canopy of natural seed-origin plantations (40 record plots in each stand) of 0.5 m2 each. Results In fresh ash-lime oak forest site, the most developed live ground cover was found under the canopy of a low-stocking 157-year-old stand (2,850 kg?ha-1), and the least developed, in a fully stocked 42-year-old stand (1,667 kg?ha-1, or 42 % less). In the 17-year-old natural young stand, which has formed after a clear sanitation felling of a 140-year-old stand with abundant herbaceous cover, the stock of live ground cover was only 9 % smaller compared to 157-year-old stand. Under the canopy of a 55-year-old fully stocked stand, the biomass of herbs was 25% less than the maximum. The moisture content of the fresh biomass of the herbaceous cover was the highest in the fully stocked, most shaded 42-year-old stand – almost 72 %. Carex pilosa Scop. (69 %) and Stellaria holostea L. (76 %), the predominant species, had the highest moisture content. In stands of another age range, the moisture content of herbs was somewhat lower, about 70 %. Stands in moist ash-lime oak forest site grow on lower, wetter parts of the slopes of northern expositions and on the ravine floor. The total projective cover of the soil by herbaceous vegetation was 50–70 %; Carex pilosa Scop., Stellaria holostea L., Asarum europaeum L., and Aegopodium podagraria L. were predominant. Conclusions Within the fresh oak forest sites, the total projective coverage of the soil with the herbaceous vegetation is greater (by 20 %) compared with wet oak forests with Carex pilosa Scop., Glechoma hederacea L., Aegopodium podagraria L. Asarum europaeum L. predominating in the composition. Herbaceous ground vegetation is an integral part of oak stands of natural seed origin and of forest ecosystems, on which both reforestation and priorities in forest management depend. 5 Tables, 13 Refs.